Pusaran Post-Truth Loyalis Gubernur Papua Lukas Enembe dalam Kasus Korupsi - Patricia Robin; Ivyela Rethalia Giroth (MUKASI: Jurnal Ilmu Komunikasi, 2023)
The advances in technology and the era of digitalization have brought people into a new situation, namely when facts are at stake. The principle of communication science that has 2 (two) sides of the message, which are the message delivered and the message received becomes increasingly biased. This is what makes a new phenomenon, post-truth increasingly widespread. Post-truth is the face of most contemporary phenomena. One of the causes is the presence of new media, where a person can become a consumer and  a producer as well. Post-truth is an expression of concern from those who care about the concept of truth and feel that concept is under attack. Indonesian media coverage in September 2022 is currently in that phase. This began with the summons of the Governor of Papua, Lukas Enembe over the alleged graft case of 1 billion Rupiah. The root of the post-truth problem occurred when loyalists staged demonstrations supporting and showing their side with Lukas Enembe. The research method that will be carried out uses a qualitative approach with descriptive presentation. The data collection technique is by interviewing, and also library research. It was found that his dedication to Papua for dozens of years made Lukas Enembe loved by his people and considered a father for the Papuan people.